Phylogenetic Discordance at the Specie Boundary: Comparative Gene Genealogies Among Rapidly Radiating Heliconius Butterlies (2012)
Recent adaptive radiations provide excellent model systems for understanding speciation, but rapid diversification can cause problems for phylogenetic inference. Here we use gene genealogies to investigate the phylogeny of recent speciation in the heliconiine butterflies. We sequenced three gene regions, intron 3 (?550 bp) of sex-linked triose-phosphate isomerase (Tpi), intron 3 (?450 bp) of autosomal mannose-phosphate isomerase (Mpi), and 1,603 bp of mitochondrial cytochrome oxidase subunits I and II (COI and COII), for 37 individuals from 25 species of Heliconius and related genera. The nuclear intron sequences evolved at rates similar to those of mitochondrial coding sequences, but the phylogenetic utility of introns was restricted to closely related geographic populations and species due to high levels of indel variation.